Pushed or pulled? Girls and boys facing early school leaving risk in Italy - Camilla Borgna; Emanuela Struffolino (Social Science Research, 2017)
Compared to girls, boys are more at risk of early school leaving. However, it is unclear whether gender differences are driven by push factors, which alienate students from the school system, or pull factors, which attract them out of it. This paper examines gender differences in early school leaving, assessing the role of previous scholastic performance, parental education, and differential employment opportunities. By analyzing two nationally representative datasets, we focus on Italy, a country with high rates of early school leaving and pronounced gender inequalities in the labor market. Our results show that gender effects are partially mediated by scholastic performance, a crucial push factor, and are stronger among low-achieving students, pointing to a higher resilience of girls to academic failure; parental education is highly protective, especially for boys. Yet, boys' higher propensity to drop out is also, at least partly, explained by better employment opportunities in the formal and informal labor market.
Keywords: 330